2021
DOI: 10.1523/eneuro.0380-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Differential Modulation of Effective Connectivity in the Brain’s Extended Face Processing System by Fearful and Sad Facial Expressions

Abstract: The processing of emotional facial expressions is underpinned by the integration of information from a distributed network of brain regions. Despite investigations into how different emotional expressions alter the functional relationships within this network, there remains limited research examining which regions drive these interactions. This study investigated effective connectivity during the processing of sad and fearful facial expressions to better understand how these stimuli differentially modulate emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 94 publications
(143 reference statements)
0
10
0
Order By: Relevance
“…Importantly, the models are limited to unidirectional influence, and the present study cannot dissociate whether information flow in a specific connection is solely unidirectional or simply stronger in one of the directions. However, prior evidence suggests that studies of effective connectivity during human development can map changes in directed information flow (acyclic) associated with emotion regulation (Jamieson et al, 2021;Jiang et al, 2019;Kadosh et al, 2016), and we note that the discovery of an age-related switch in the dominance of information flow provides critical insight into frontoamygdala development regardless of whether that dominance reflects an underlying unidirectional or bidirectional connection. Though the sample size in the present pilot study is limited, the IMaGES approach is the only effective connectivity method to aggregate across participants, thus maximizing statistical power (i.e., the effective sample size is the number of timepoints × participants).…”
Section: Discussionmentioning
confidence: 61%
“…Importantly, the models are limited to unidirectional influence, and the present study cannot dissociate whether information flow in a specific connection is solely unidirectional or simply stronger in one of the directions. However, prior evidence suggests that studies of effective connectivity during human development can map changes in directed information flow (acyclic) associated with emotion regulation (Jamieson et al, 2021;Jiang et al, 2019;Kadosh et al, 2016), and we note that the discovery of an age-related switch in the dominance of information flow provides critical insight into frontoamygdala development regardless of whether that dominance reflects an underlying unidirectional or bidirectional connection. Though the sample size in the present pilot study is limited, the IMaGES approach is the only effective connectivity method to aggregate across participants, thus maximizing statistical power (i.e., the effective sample size is the number of timepoints × participants).…”
Section: Discussionmentioning
confidence: 61%
“…22 Functional MRI has shown that the amygdala responds differentially to fearful versus happy facial expressions, depending on attentional processes. 23 Thus, the impaired fear recognition resulting from the amygdala damage seems to be due to its failure in directing the visual system to search, fixate, pay attention and use such information to identify emotions. 24…”
Section: Discussionmentioning
confidence: 99%
“…22 Functional MRI has shown that the amygdala responds differentially to fearful versus happy facial expressions, depending on attentional processes. 23 Thus, the impaired fear recognition resulting from the amygdala damage seems to be due to its failure in directing the visual system to search, fixate, pay attention and use such information to identify emotions. 24 The findings of the present case were in line with other research that has shown that bilateral damage to the medial temporal lobe, including the amygdala and not just hippocampal damage, is associated with alterations in autobiographical recollections.…”
Section: Discussionmentioning
confidence: 99%
“…(2000) , and assessed implicit emotional processing to negatively valanced facial stimuli. The task has been examined in previous work by our group ( Jamieson et al. 2021 ).…”
Section: Methodsmentioning
confidence: 99%